Síndrome de sepsis grave post Esplenectomia (OPSI), reporte de un caso más revisión de la literatura. Nova Clínica S.A.: Sepsis severe post splenectomy symposium (OPSI), report of a case more review of the literature. Nova Clinica S.A. (La U Investiga, 2017)
This syndrome defines: to all sepsis, severe sepsis, severe pneumonia and secondary meningitis toencapsulated bacteria, viruses, parasites, protozoa, in patients with a history of asplenia orhyposplenism that can be colonized by encapsulated microorganisms (streptococci Pneumoniae, Haemophilus Influenza type B, Neisseria meningitidis), with a predisposition 12 to 25 times higher inrelation to the general population and associated with mortality greater than 80% 1-2-3.The case of a male patient aged 55 with a history of splenectomy 30 years without further immunization who attends a private institution (NOVA CLINIC SA) of the city of Quito-Ecuador for attention after presenting several months level occurs unexplained skin petechiae. Suddenly and after food intake presented and developed an important reason admission to emergency and subsequent gastrointestinal syndrome in the intensive care unit after study is pigeonholed the patient under the box syndrome splenectomy sepsis post (OPSI). Splenectomyis a common surgical procedure in the country and is given by various causes including severe abdominal trauma. The case presented and developed in this opportunity is a clear reflection of misinformation and lack of adherence to followup all patients with asplenia and hyposplenia should have this disease has a high mortality rate in the early hours and could cause severe morbidity or disability if the necessary support is not provided.
Keywords: Sepsis; post splenectomy; Streptococcus pneumoniae